Note on controllability of linear fractional dynamical systems. Issue 4 (1st October 2016) - Balachandran, K.; Matar, M.; Trujillo, J. J.
Abstract : In this article, we obtain the solutions of some fractional differential systems with different orders using the inverse operator method and Mittag–Leffler function. Moreover, the controllability of time-invariant linear fractional system is investigated. Some examples are provided to illustrate the theory.